Music Talks with Children - Tapper, Thomas, 1864-1958 (Salt Lake City, UT : Project Gutenberg, 2004)
"Music Talks with Children" by Thomas Tapper is an educational guide written in the late 19th century. This work aims to engage children in conversations about music, highlighting its beauty, significance, and the joy that can come from active participation rather than mere rote learning. Tapper emphasizes the importance of music as an art form that nurtures joy, order, and a sense of community, challenging conventional notions about children's capability to understand and appreciate music deeply. The opening of the book sets a reflective tone, beginning with children's innocence in discovering music and the challenges they face in their learning journeys. Tapper illustrates through a dialogue between a master and a child that genuine understanding and appreciation of music come from the heart and not superficial examination. He aims to encourage children to see music as a source of inner light and happiness. Furthermore, he stresses the significance of diligence, selfless service to others, and the joy found in music, framing these discussions in the context of personal growth and emotional connection with the art form. (This is an automatically generated summary.)
Release date is 2004-12-13
E-text prepared by David Newman, Keith M. Eckrich, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Music -- Instruction and study